ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA : Studi Kasus pada Desa-Desa di Kecamatam Selat Kabupaten Karangasem - Ni Luh Putu Ita Sulistiyawati (Universitas Triatma Mulya, 2021)
This study aims to determine the accountability of village fund management in realizing good village financial governance in Selat District. This study uses a qualitative method with a phenomenological approach. The results showed that the village fund management accountability system in Selat District was already based on the principle of accountability and the principle of responsibility, although it had not fully demonstrated transparency and community participation. So that not all village communities know about the development activities carried out by village officials and cause the community to think these activities are projects. The village treasurer does not yet understand accountability, so in making reports the village financial system application is assisted. The reasons for not optimal transparency and accountability in the management of village funds are first, the competence of human resources is still low as seen from the education level of village government officials who are the spearhead of the implementation of Village Fund management. Second, the lack of effective guidance from the District and Regency governments in guiding village officials. Based on this, it is necessary to have the efforts and commitment of the Village Government and District Government officials related to increasing the capacity of Village Government officials and increasing the capacity of the BPD to maximize the role and function of the BPD in monitoring the implementation of Village Fund management.